2017
DOI: 10.1128/aem.00668-17
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl Analogue of Mutacin 1140, a Scaffold for Lead Antibacterial Discovery

Abstract: Mutacin 1140 belongs to the epidermin group of lantibiotics. Epidermin class lantibiotics are ribosomally synthesized and posttranslationally modified antibiotics with potent activity against Gram-positive bacteria. In particular, this class is effective at targeting drug-resistant Streptococcus pneumoniae, methicillin-resistant Staphylococcus aureus (MRSA), Mycobacterium tuberculosis, and Clostridium difficile.residue is derived from a decarboxylation of a terminal cysteine that is involved in lanthionine rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
1
10
0
1
Order By: Relevance
“…Prior to the synthesis of bicyclic C/D ring, the AviCys was modified at position 22 to a cysteamine because it was previously shown that the AviCys functional group may not be essential for optimal antimicrobial activity (Figure B) . This modification simplifies the synthetic strategy and allows to confirm whether or not an cysteamine can indeed replace an AviCys and confirms the impact of this substitution on biological activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior to the synthesis of bicyclic C/D ring, the AviCys was modified at position 22 to a cysteamine because it was previously shown that the AviCys functional group may not be essential for optimal antimicrobial activity (Figure B) . This modification simplifies the synthetic strategy and allows to confirm whether or not an cysteamine can indeed replace an AviCys and confirms the impact of this substitution on biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the synthesis of bicyclic C/D ring, the AviCys was modified at position 22 to a cysteamine because it was previously shown that the AviCys functional group may not be essential for optimal antimicrobial activity ( Figure 1B). 43 This modification simplifies the synthetic The building block lanthionine 7 precursor was synthesized as previously reported, [10][11][12] which was then followed by esterification to yield lanthionine OPfp ester 7. Compound 7 was used as presented in Scheme 2.…”
Section: Synthesis Of Lanthionine Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipid II binding assay. A lipid II binding assay using a thin-layer chromatography (TLC) procedure was performed as previously described (48). Briefly, the mobile solvent used consisted of butanol-acetic acid-water-pyridine in a 15:3:12:10 volume ratio.…”
Section: Methodsmentioning
confidence: 99%